Pengunaan Metode Diskusi Untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam di SDN 13 Lubuk Nyiur - Yulinda, Yulinda (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ learning achievement in Islamic Education through the application of the discussion method in class IV SDN 13 Lubuk Nyiur. This research uses a Classroom Action Research (CAR) approach with two cycles. The results show that, despite some challenges in student participation and motivation during the first cycle, significant improvement was observed in the second cycle. All students in the second cycle achieved learning completeness, with a significant increase in the average score. The implementation of the discussion method proved to be effective in enhancing students’ readiness and learning achievement, as well as creating a more interactive and enjoyable learning environment.